The Optimization of Power Generation Mix To Achieve Net Zero Emission Pathway in Indonesia Without Specific Time Target - Fitriana, Ira; Hadiyanto; Warsito, Budi; Himawan, Edi; Santosa, Joko (International Journal of Sustainable Energy Planning and Management, 2024)
Indonesia is committed to achieving Net Zero Emission (NZE) conditions by the year 2060, with policy adjustments and constraints being necessary to realize this goal. The aim of this study is to achieve NZE conditions using a least-cost optimization method for various power plants that rely on fossil and non-renewable energy sources, without specifying a target year. Two scenarios, Business as Usual (BAU) and NZE, were developed for comparison in the optimization analysis. Through the utilization of LEAP and NEMO software, the optimization results suggest that optimal NZE conditions in Indonesia could be attained by 2075, with solar-based electricity generation playing a crucial role in meeting basic electricity demands. The NZE scenario predicts a 28% rise in electricity demand by 2100 compared to the BAU scenario. In 2075, PV will contribute 32.8% (224.3 GW) to total power supply, while BESS will provide 198.8 GW according to the NZE scenario. This study aims to assist the Indonesian government and stakeholders in reaching the NZE goal, while maintaining current efforts to avoid new efficiency and financial challenges. Achieving this goal will involve using a cost-effective optimization approach and implementing energy-efficient technologies and conservation programs.